Endoscopy Video 2018
DOI: 10.1136/gutjnl-2018-bsgabstracts.102
|View full text |Cite
|
Sign up to set email alerts
|

PTH-079 Fully covered metal stent insertion for the treatment of refractory post endoscopic sphincterotomy bleeding

Abstract: colonoscopic technique from Taiwan which facilitates easier placement of the snare thereby achieving en-bloc resection. Methods A 67 year old lady presented to our institute with an altered bowel habit and was found to have a flat polyp in the sigmoid colon on colonoscopy. Results Standard injection as per conventional endoscopic mucosal resection was initially performed. Then a suitably sized snare was selected and the snare tip was used to make a single incision with cut current lateral to the polyp. The sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Over the last decade, several series and small cohort studies have reported utilizing fully covered self-expanding metal stents (FCSEMS) to achieve hemostasis in severe cases of EBSrelated bleeding that were refractory to traditional management [18][19][20][21][22][23]. A recent retrospective study compared FCSEMS to traditional endoscopic modalities for the management of EBS-related bleeding after failure of traditional endoscopic modalities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, several series and small cohort studies have reported utilizing fully covered self-expanding metal stents (FCSEMS) to achieve hemostasis in severe cases of EBSrelated bleeding that were refractory to traditional management [18][19][20][21][22][23]. A recent retrospective study compared FCSEMS to traditional endoscopic modalities for the management of EBS-related bleeding after failure of traditional endoscopic modalities [20].…”
Section: Introductionmentioning
confidence: 99%